The impact of assembly robot orientation errors on the assembly of parts with fl at surfaces - Kluz, Rafał; Bucior, Magdalena; Kubit, Andrzej; Wydrzyński, Dawid (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2018)
This paper presents the phenomena occurring during the mating of machine parts with fl at surfaces. The requirements have to be fulfilled in order for the connection to be carried out correctly were formulated. Then, in relation to these requirements, the impact of robot errors on the probability of correct implementation of the connection process of the considered machine parts was determined. It was shown that if the dimensions of the parts to be joined are small, (≤ 20 mm), the effect of robot orientation errors can be neglected under mounting conditions. Although this slightly reduces the accuracy of the probability of combining parts (0.5%), it considerably simplifies them. It has also been shown that in the case of larger parts dimensions, it is necessary to take into account angular errors but only those that cause displacement of the surfaces of the largest lengths. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)